2012
DOI: 10.1186/1447-056x-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carpal tunnel syndrome on the expectant woman's life

Abstract: IntroductionCarpal Tunnel Syndrome is known to be a common complication during pregnancy especially during the third trimester.AimThis article focuses on its impact to the third trimester pregnant mothers with CTS.MethodsThird trimester pregnant mothers with no other known risk factors for CTS, were interviewed and examined for a clinical diagnosis of CTS. The severity of CTS was assessed by means of symptoms severity and functionality using the Boston Carpal Tunnel Questionnaire.ResultsOut of 333 third trimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…These findings were comparable to the previous some studies. [17,18] We found that 90 (45%) women were educated and 70 (35%) were from urban areas. Research that used electrodiagnosis found a high prevalence of CTS in pregnancy; whereas, studies that used solely clinical diagnostics found a low prevalence of CTS in pregnancy.…”
Section: Discussionmentioning
confidence: 84%
“…These findings were comparable to the previous some studies. [17,18] We found that 90 (45%) women were educated and 70 (35%) were from urban areas. Research that used electrodiagnosis found a high prevalence of CTS in pregnancy; whereas, studies that used solely clinical diagnostics found a low prevalence of CTS in pregnancy.…”
Section: Discussionmentioning
confidence: 84%
“…Picky eating is a common eating behavior among children [ 1 , 2 , 3 , 4 , 5 , 6 ], often causing considerable stress to parents and caregivers [ 6 ]. Children exhibiting picky eating behavior often demonstrate strong food preferences and rejection of particular foods or food texture [ 7 ], which may lead to limited dietary variety and possibly inadequate or unhealthy diet [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the prevalence of picky eaters was estimated as 89.8% [ 2 ]. Other studies reported rates of picky eaters ranging from 13 to 47.4% [ 3 , 4 , 5 , 6 ]. As such, many studies have been devoted to understanding the factors associated with picky eating.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced HGS is characterised by pain, numbness, difficulty in grasping objects, muscle weakness and tendency of things to drop from the hand [6,20]. However, pregnant women require good HGS to carry out their daily living activities such as eating, washing, writing and grooming.…”
Section: Introductionmentioning
confidence: 99%